Application of The Peer Tutor Method to Improve Mathematical Communication Skills in Class X Students - Khomsyatun, Siti Hazar (Universitas Wiralodra, 2023)
This study aims to determine students' mathematical communication abilities through peer tutoring methods. The research method used is experimental research with a research design that is one group pretest-posttest. The population and sample of this study were class X MIPA students of SMAN 1 Lelea with a total of 20 students. The technique used in determining the sample is by using non-probability sampling technique. The instruments used in this study were test sheets for mathematical communication skills and student response questionnaires. The results showed that learning mathematics using peer tutoring methods can provide maximum results, namely that students' mathematical communication skills can increase, based on the average N-gain score of 0.72 in the high category. In addition, the results of the study also show that learning mathematics using peer tutoring methods can improve students' mathematical communication skills significantly. From the results of the N-gain test obtained, the peer tutor learning method can improve students' mathematical communication abilities. And for the results of the students' responses, namely students giving a good response to learning using the peer tutoring method with an average percentage of students using the peer tutoring method of 68.85%. Based on the results of the research that has been done, it can be concluded that this peer tutoring method can be used in learning mathematics in the classroom.